Media Framing of Minorities' Crisis: A Study on Aljazeera and BBC News Coverage of the Rohingya - Kanaker, Osama; Abughazlih, Mohamed Oklah; Mohd Faizal Kasmani (Natl Univ Malaysia, Fac Social Sciences & Humanities, 2024)
Indexed by WOS